Fatores de risco para o desenvolvimento de crianças atendidas em Unidades de Saúde da Família, ao final do primeiro ano de vida: Aspectos sociodemográficos e de saúde mental materna - Ribeiro, Débora Gerardo; Perosa, Gimol Benzaquen; Padovani, Flávia Helena Pereira (FapUNIFESP (SciELO), 2014)
The scope of this article is to evaluate risk and protection factors for the development of 1-year-olds assisted at family health care units. It is a cross-sectional study involving 65 children of approximately 1 year of age and their mothers attended at two family health care units. The development was assessed using a developmental screening test (Denver II). The mothers filled out the SRQ-20 questionnaire to identify common mental disorder (CMD) indicators. After data collection, descriptive and inferential statistical analysis was performed. Global development was at risk in 43.1% of the children evaluated, and the most affected areas were language and fine motor development; 44.6% of mothers had results indicative of CMD when the child was 1 year of age. In bivariate analysis, reported depression, smoking, infections in pregnancy, CMD after birth and working outside the home were significantly associated with the children's development. After full statistical analysis, CMD was revealed as being a risk factor, and working away from home as being a protection factor. In order to increase the chances of success of programs targeted for children at health care units and avoiding the risk of impaired development, it is important to focus on two aspects: children's stimulation and maternal mental health.
Risk factors for impaired development in children attended at family health units at the end of the first year of life: Socio-demographic aspects and maternal mental health
Keywords: Child development; Maternal mental health; Risk factors